Ophthalmological and Clinical and Biochemical Characteristics of Patients with Essential Arterial Hypertension (Eurasian Medical Research Periodical, 2022)
It is known that ONH drusen are diagnosed in 4% of cases in healthy adults and represent deposits of chondroitin sulfates prone to progressive calcification with age [110, 111, 131, 138,214]. As a rule, they are found in both eyes, but at the same time they are located asymmetrically [14]. They occur equally often in both men and women and can often potentiate such serious complications as: peripapillary hemorrhages (including massive ones), peripapillary subretinal neovascular membranes, intraretinal extravasation of blood plasma, damage to the pigment epithelium in the macula and papillomacular bundle [10] . At the same time, information about the presence of optic disc drusen and their complications in children, according to the literature, is isolated [1].